Implementing think-pair-share technique in discussing know about business module to enhance students’ ability in reading comprehension - Fitrotul Maulidiyah; Noverita Wahyuningsih (Jurnal Linguistik Terapan, 2019)
This study is completed to implement think-pair-share technique in discussing Know about Business module to enhance students’ ability in reading comprehension. This study was triggered by phenomena found in the classroom where students cannot understand reading texts thoroughly especially when it comes to difficult words and relationship among sentences in the reading texts. The implementation of Know about Business module which has a topic of entrepreneurship is expected to improve students’ learning interest especially in relation with reading skill. This study implements classroom action research methodology. In planning, teacher will prepare for a teaching scenario and learning materials which will be used in the classroom. In implementation, teacher will implement think-pair-share technique in Reading I course subject. During the think phase, teacher will give brainstorming questions so that students will be motivated to think critically. In this phase, students are now allowed to discuss with their friends. During the pair phase, students will gather in some small groups to further discuss the results of their critical thinking in the classroom. The next phase is share and it is when the students express their results of discussion in the classroom. The next phase of classroom action research is observation. In this phase, teacher will observe how the students’ progress is after the implementation of think-pair-share. If students have made progress, teacher will go on to the final phase which is reflection. Results of the research showed that reading comprehension of 1A English department students at Politeknik Negeri Malang improved through the implementation think-pair-share technique using Know about Business module. Students’ reading scores mean improved from 56.8 to 75.7 and all students could pass the reading comprehension passing grade. Results from the questionnaires also illustrated that students showed interests and enthusiasm in doing reading activities using think-pair-share techniques with the use of Know about Business module.